Revolutionizing concrete through sustainable Practices: a performance study on strength variation under acidic environments - B. Narendra Kumar; P. Sai Vineela; Dhanalakshmi Kiran Bhat (Discover Sustainability)
Abstract The construction sector continues to draw excessive natural resources for raw materials through extraction processes which leads to environmental concerns about its waste disposal of Construction and Demolition materials. The adoption of environmentally friendly concrete systems serves as a realistic method to address existing issues. The research project determines concrete optimization through the utilization of Fly Ash together with Ground Granulated Blast Furnace Slag and M-sand as well as recycled fine and coarse aggregates. The primary objective of this research work consists of studying both the mechanical characteristics and durability performance of sustainable concrete mixes for construction applications. The researchers developed concrete mixes of M25, M40, and M60 grades through the utilization of recycled materials. All tests for assessing mechanical properties evaluated compressive strength with flexural strength and split tensile strength. The research evaluated concrete durability through two tests namely Rapid Chloride Permeability Test and Acid Attack Tests. The deflection characteristics under designed loads were evaluated through reinforced concrete beam and column castings that served to measure structural performance. The concrete mixes experienced good workability while simultaneously showing remarkable enhancements in their mechanical properties. Construction and Demolition Waste materials utilized in M25 and M60 concrete exhibits excellent performance in split tensile strength measurements. The resistance of both M25 and M60 concrete to applied pressure reached high levels, allowing them to serve as suitable materials for structural work. Scientific investigations show that incorporating recycled waste materials for concrete production brings both environmental sustainability and design quality performance objectives.